Serum Total Sialic Acid as a Novel Complementary Candidate Marker of Hepatic Damage in Obstructive Jaundice - (:unkn) unknown (ASSOC CLINICAL SCIENTISTS, 2014)
Background: The present study was carried out to investigate oxidant-antioxidant status and serum total sialic acid (SA) levels as alternative markers complementary to routine laboratory tests in an experimental obstructive jaundice model (OJM). Rats were divided into three groups: sham operated control (SOC), OJM monitored for 7 days (OJM-7), and OJM monitored for 14 days (OJM-14). Antioxidant activities, lipid peroxidation, C reactive protein (CRP), and SA concentrations were analyzed at the end of post-operative days 7 and 14. In both OJM groups, SA and CRP levels were significantly increased when compared with the SOC group. Moreover SA and CRP levels were significantly correlated in both groups. As a marker of inflammation and oxidative stress in obstructive jaundice, serum SA may serve as an adjunct when combined with other markers in disease screening and progression.
Keywords: Sialic acid; C reactive protein; cholestasis; oxidative stress; antioxidants; rat; BILE-DUCT LIGATION; CHOLESTASIS; LIVER; RATS; DISEASE; MYELOPEROXIDASE; INFLAMMATION; ENDOTOXIN; PROTEIN; PLASMA